Major factors influencing breastfeeding practice among Indian mothers in estates , 1997 - Malliga a/p Sellapan,; Khadijah Shamsuddin, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2006)
A cross-sectional study to measure the prevalence of breastfeeding and identify factors influencing breastfeeding among Indian women in estates was carried out in 6 randomly selected estates in the Larut Matang, Selama District. Sample consisted of all Indian women with live children less than 2 years of age in December 1996. A total of 228 mothers were identified, and the response rate was 100%. Results showed that 74.1% initiated breastfeeding but only 9.7% continued to breastfeed for more than 4 months. Compared to mothers who did not breastfeed, more women who breastfed were between 20-34 years of age, had some form of education, were not working and had a family income of RM. 500-1000. Breastfeeding initiation was also higher among those whose utilisation of the health care services was more frequent but not for the other aspects of health service utilisation. However these factors were not statistically significant. In this study, among mothers who breastfed their infants, 55% had good knowledge on breastmilk and 53.3% were found to have positive attitude towards breastfeeding. Two main reasons given by mothers for not breastfeeding were work and insufficient milk.